2020
DOI: 10.1186/s12917-020-02502-4
|View full text |Cite
|
Sign up to set email alerts
|

A ‘what-if’ scenario: Nipah virus attacks pig trade chains in Thailand

Abstract: Background: Nipah virus (NiV) is a fatal zoonotic agent that was first identified amongst pig farmers in Malaysia in 1998, in an outbreak that resulted in 105 fatal human cases. That epidemic arose from a chain of infection, initiating from bats to pigs, and which then spilled over from pigs to humans. In Thailand, bat-pig-human communities can be observed across the country, particularly in the central plain. The present study therefore aimed to identify highrisk areas for potential NiV outbreaks and to model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Importing infected pigs from a contaminated area in Malaysia infected 11 slaughterhouse workers and caused one death [15,23,25]. Based on these outbreaks, a study aimed to identify the potential threat of pig trading in the transmission of NiV and examined how long-distance transportations of living pigs may facilitate disease dissemination in Thailand [55]. Findings showed that, although the risk of NiV dissemination through pig trade is low, it is not negligible and may cause local outbreaks that requires preventive strategies concerning international trading [55].…”
Section: Transmission Of Henipavirusesmentioning
confidence: 99%
“…Importing infected pigs from a contaminated area in Malaysia infected 11 slaughterhouse workers and caused one death [15,23,25]. Based on these outbreaks, a study aimed to identify the potential threat of pig trading in the transmission of NiV and examined how long-distance transportations of living pigs may facilitate disease dissemination in Thailand [55]. Findings showed that, although the risk of NiV dissemination through pig trade is low, it is not negligible and may cause local outbreaks that requires preventive strategies concerning international trading [55].…”
Section: Transmission Of Henipavirusesmentioning
confidence: 99%
“…In many cases, livestock production creates an important conduit between diseases in wildlife and humans. For instance, Nipah virus in Southeast Asia, a disease of bats, entered humans via pig production in peri-urban areas where bats roosted in trees over pig pens, and so the pigs ingested bat feces containing the virus, which was then passed on to humans (Wongnak et al, 2020).…”
Section: Agriculture and Infectious Diseasementioning
confidence: 99%